فتح مکہ میں آنحضرت ﷺکا سیاسی کردار: Political role OF Holy Prophet (PBUH) in the conquest of Makkah (Khairulummah, 2021)
The conquest of Makkah is an extraordinary and unprecedented event of the Muslim history in which the Holy Prophet (PBUH) demonstrated his political discernment and strategy that Islam is an unassailable entity that can never be eradicated. Your democratic engagement in the conquest of Makkah facilitated the establishment of a government of peace and reconciliation in Arabia, which led the Arabs to grow submissive to the Sharia. They all became Muslims as a consequence of your political participation; hence, Makkah's government was then altered and structured accordingly with Islamic principles.The political role of the Holy Prophet (PBUH) in the conquest of Makkah has been addressed in this article. The methodology chosen to go ahead with this piece was astounding. However, the challenge faced during the research was: Muslims in the modern age encounter a slew of political issues. And as a result, Politicians, if they try, can overcome their challenges by remembering the Holy Prophet's (PBUH) political involvement in the Conquest of Makkah.Keywords: The Holy Prophet (PBUH), political problems , The Conquest of Makkah, Modern era.